Efektivitas Konseling Eksistensial Humanistik Untuk Mengatasi Nomophobia Pada Remaja - Putri, Wahyuni Ade Futri (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2025)
impact that is detrimental to themselves and others. dependence on smartphone communication technology known as Nomophobia or No Mobile Phone Phobia. The purpose of this study was to overcome nomophobia (no mobile phone phobia) among adolescents in Dusun Data with humanistic existential counseling services. This research is a type of quantitative research with experimental methods. Data collection techniques used are observation, interviews, and questionnaires. The population in this study amounted to 21 teenagers and the sample was taken using a purposive sampling technique, so that the research sample consisted of 8 teenagers. The results of this study indicate that there is a decrease in the level of nomophobia which can be seen from the results of the pre-test questionnaire where the pre-test questionnaire score was 724 with an average of 90.05 and the post-test questionnaire score was 540 with an average of 67.5. So it can be concluded that the null hypothesis is rejected and the alternative hypothesis is accepted, namely humanistic existential counseling services are effective in overcoming the problem of nomophobia in adolescents in Data Hamlet, Tokkonan Village, Enrekang Regency. Keywords:Humanistic Eksistensial Humanistik, Nomophobia, Teenager